The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/separations4040037
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Separation of Seed Oil Triglycerides Containing Isomeric Conjugated Octadecatrienoic Acid Moieties by Reversed-Phase HPLC

Abstract: Abstract:Relative retention analysis and increment approach were applied for the comparison of triglycerides (TGs) retention of a broad set of plant seed oils with isomeric conjugated octadecatrienoic acids (CLnA) by reversed-phase HPLC for "propanol-2-acetonitrile" mobile phases and Kromasil 100-5C18 stationary phase with diode array detection (DAD) and mass spectrometric (MS) detection. The subjects of investigation were TGs of seed oils: Calendula officinalis, Catalpa ovata, Jacaranda mimosifolia, Centranth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
6
0
3
Order By: Relevance
“…Thus, first of all, octadecatrienoic acid was proved to be a catalpic one. Then the increment for the replacement of linoleic with (9-trans,12-trans)-octadeca-9,12-dienoic acid substituents, found for catalpa seed oil TAGs [14], coincides with the increment ∆ (L→ Y) being the sum of two consecutive increments ∆(L → X) and ∆(X → Y) for Chilopsis linearis oil TAG. Thus, acid Y is the (9-trans,12-trans)-octadeca-9,12-dienoic acid substituent.…”
Section: Determination Of the Tag Typementioning
confidence: 59%
See 1 more Smart Citation
“…Thus, first of all, octadecatrienoic acid was proved to be a catalpic one. Then the increment for the replacement of linoleic with (9-trans,12-trans)-octadeca-9,12-dienoic acid substituents, found for catalpa seed oil TAGs [14], coincides with the increment ∆ (L→ Y) being the sum of two consecutive increments ∆(L → X) and ∆(X → Y) for Chilopsis linearis oil TAG. Thus, acid Y is the (9-trans,12-trans)-octadeca-9,12-dienoic acid substituent.…”
Section: Determination Of the Tag Typementioning
confidence: 59%
“…To determine the specific TAGs of Chilopsis linearis seed oil, chromatograms were registered at two wavelengths with subsequent comparison with the chromatogram of the catalpa seed oil. The composition of the latter oil had been determined by us earlier [14].…”
Section: Determination Of the Tag Typementioning
confidence: 99%
“…In our preliminary study 17 , we reported that the molar fraction of punicic acid of Thladiantha dubia seed oil slightly exceeds 35 . In the present work, composition of 15 TAGs that are listed in Fig.…”
Section: Determination Of Compositions Tags Of Thladianthamentioning
confidence: 85%
“…The spectra of Thladiantha seed oils Fig. 1 is characterized by the absorption maxima at 263, 272 and 283 nm, being characteristic to that of conjugated trienoic compound 17 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the two positional isomers trans,trans,cis-8,10,12-octadecatrienoic acid (calendic acid) and cis, trans,cis-8,10,12-octadecatrienoic acid (jacaric acid) (Fig. 1) have been identified in some Calendula and Jacaranda species (Chisholm and Hopkins 1965;Dulf et al 2013;Nguyen et al 2017).…”
Section: Conjugated Acetylenic Fatty Acidsmentioning
confidence: 99%